Towards a pragmatic approach to translation: Bridging cultural and linguistic gaps - Ahmad H.Osman, Rahmah; Jaffer, Usman; Hamawiya, Adham Muhammad Ali; Sha'ari, Badrul Aini; Che Amran, Aisyah Aminah; Zulqurnain, Ajwad Mohd; Zakaria, Ahmad Lutfi (Global Academic Excellence, 2024)
This studyadvocates for a pragmatic approach to translation in the modern era, addressing challenges arising from linguistic diversity, cultural nuances, and technological advancements. Through a comprehensive literature review and analysis of case studies, this research establishes the need for a methodology that integrates contextual analysis, cultural adaptability, theoretical frameworks, and strategic technology utilization. This approach emphasizes the translator's role as a cultural mediator, bridging gaps andensuring effective communication across diverse audiences. By examining the implications of pragmatic translation in education, business, diplomacy, media, and technology, this study highlights its transformative potential in fostering accessibility, cultural exchange, and collaboration. Furthermore, it explores future directions, including the integration of emerging technologies, ethical considerations, development of multilingual resources, and promotion of translation as a vital skill in an increasingly interconnected world. This research underscores the importance of pragmatic translation in facilitating global understanding and contributing to a more inclusive and harmonious global community.